1987
DOI: 10.1111/j.1365-2427.1987.tb01319.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of the three‐spined stickleback, Gasterosteus aculeatus L., in the River Weaver, England

Abstract: 1. The production of three-spined sticklebacks, Gastero.steus aculeatus, estimated in the margin of a large cbannelized lowland river, averaged 42.3 g m"^ yr~' and the P/B ratio was 3.7. The production value greatly exceeds those previously recorded for G. aculeatus and results from tbe very high population densities.2. Life-bistory tactics of tbe sticklebacks included both r-and K-selected traits.3. Tbe fish were carnivorous in tbe summer months but predominantly detritivorous in the winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
1
6
0
1
Order By: Relevance
“…These observations are consistent with previous reports of the age structure (Mann, 1971;Allen and Wootton, 1982;O'Hara and Penczak, 1987;Wootton and Smith, 2000;Poizat et al, 2002;Wootton, 2007) and sex ratio (Kynard, 1978;Wootton, 1984;Mori, 1993;Arnold et al, 2003) of three-spined stickleback populations. Disproportionate mortality among males due to the energetic demands and risks associated with male parental investment has been suggested to account for the female bias (Chellappa et al, 1989;Arnold et al, 2003).…”
Section: Population Structuresupporting
confidence: 83%
See 3 more Smart Citations
“…These observations are consistent with previous reports of the age structure (Mann, 1971;Allen and Wootton, 1982;O'Hara and Penczak, 1987;Wootton and Smith, 2000;Poizat et al, 2002;Wootton, 2007) and sex ratio (Kynard, 1978;Wootton, 1984;Mori, 1993;Arnold et al, 2003) of three-spined stickleback populations. Disproportionate mortality among males due to the energetic demands and risks associated with male parental investment has been suggested to account for the female bias (Chellappa et al, 1989;Arnold et al, 2003).…”
Section: Population Structuresupporting
confidence: 83%
“…The length frequency distributions for fish in the R. Ock suggested that 1+ adults were present throughout the summer months as is the case in some other UK stickleback populations (Allen and Wootton, 1982;O'Hara and Penczak, 1987). …”
Section: Body Mass Fork Length and Specific Growth Ratementioning
confidence: 97%
See 2 more Smart Citations
“…A produção de peixes tem sido objeto de diversos estudos em lagos (RYDER, 1965;DIANA, 1983;KELSO, 1988;RANDAL et al, 1995) e riachos (HOPKINS, 1971;PENCZAK, 1981;NEVES & PARDUE, 1983;WATERS, 1983;WHITWORTH & STRANGE, 1983;PENCZAK et al, 1985;MANN & PENCZAK, 1986;O'HARA & PENCZAK, 1987;NEWMAN & WATERS, 1989;PENCZAK, 1992) de regiões temperadas, porém são poucos os estudos realizados em outras regiões (BISHOP, 1973;KAPETSKY, 1974;WATSON & BALON, 1984;PENCZAK & LASSO, 1991). Para peixes tropicais brasileiros, apenas dois trabalhos estão disponíveis na literatura (i.e.…”
Section: Palavras-chaveunclassified